A 220ka terrestrial δ18O and deuterium excess biomarker record from an eolian permafrost paleosol sequence, NE-Siberia - Zech, Michael; Tuthorn, Mario; Detsch, Florian; Rozanski, Kazimierz; Zech, Roland; Zöller, Ludwig; Zech, Wolfgang; Glaser, Bruno (Chemical Geology, 2013)
ISSN:0009-2541 ISSN:1872-6836